Jenis Persalinan dan Produksi Air Susu Ibu di Puskesmas Gunung Medan - Evin Noviana Sari; Sri Andar Puji Astuti; Embun Nadya (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Laparotomy surgery will cause surgical wounds that will give pain. One way to deal with pain is to breathe deeply. The purpose of this study was to determine the effect of slow breathing on the recurrence of pain in post-laparotomy patients. The research design used was one group pretest-posttest, which involved 18 patients selected by accidental sampling technique. The level of pain was measured by a questionnaire, namely the Numeric Rating Scale (NRS). Data were analyzed using paired sample t-test. The results of the analysis showed that the p value <0.05, so it can be interpreted that there is a difference in the level of pain between before and after slow breathing. Furthermore, it was concluded that slow breathing is effective for reducing pain recurrence in post-laparotomy patients aged adolescents.Keywords: slow breathing; post laparotomy; teenage age ABSTRAK Kegagalan proses menyusui dapat disebabkan oleh faktor ibu, faktor bayi, faktor psikologis, faktor sosial budaya, dan tenaga kesehatan. Tujuan penelitian ini adalah untuk mengetahui hubungan antara jenis persalinan dengan produksi air susu ibu pada masa menyusui. Desain penelitian ini adalah cross-sectional. Pengumpulan data dilakukan menggunakan kuisioner, lalu dianalisis menggunakan uji Chi-square.  Hasil analisis menunjukkan nilai p = 0,000. Selanjutnya disimpulkan bahwa ada hubungan antara jenis persalinan dan produksi air susu ibu.Kata kunci: jenis persalinan; menyusui; produksi air susu ibu